Endoillumination Assisted Phacoemulsification in Patients with Hazy Cornea - Mohamed Hagag; Basheer Abo-Elfotouh Eltantawy; Akram Fekry Elgazar; Nour Eldin Abd-Elhamid Abd-Elhalim; Younes Abdel Elhafez (International Journal of Medical Arts, 2022)
Background: Worldwide, cataract is the main cause of blindness. It accounts for 55% of 41 million blind. Visual restoring is made by cataract surgery.The aim of the work: This study designed to evaluate the use of endoillumination system in phacoemulsification in patients with hazy cornea and to assess its efficacy, complications, and the best way of using it.Patients and Methods: A prospective study included 40 eyes with cataract and hazy cornea were scheduled for cataract surgery, at Al-Azhar University Hospital [Damietta]. A comparison was made during each step of phacoemulsification with and without endoillumination. The post-operative assessment was performed on the first day, at the end of the first week, the first month, and the third month after phacoemulsification by best corrected visual acuity [BCVA], slit-lamp bio-microscopy and intraocular pressure measurement.Results: The mean age was 68.1 years; 28 patients were females and 26 had operation in the right eye. Capsulorhexis with illumination showed good results among 8 patients, 8 showed no change, and only two patients were worsened. However, without illumination, 16 patients had good results and 6 showed no improvement without any significant difference. In hydrodissection with illumination, 6 had good results and 4 showed no change. But, without illumination, 16 had good results, and 8 showed no improvement. The nucleus fragmentation with illumination revealed excellent results in 24 patients. However, without illumination, two patients had good results, 8 cases showed no improvement, and only two patients were worsened with a significant difference.Conclusion: Intracameral endoillumination improves the visual quality particularly the step of the nucleus fragmentation during cataract surgery.